BERND HANSEN / DIRK SCHÜSSLER-LANGEHEINE (eds.), Patent Practice in Japan and Europe – Liber Amicorum for Guntram Rahn - Ganea, Peter (Zeitschrift für Japanisches Recht, 2011)
BERND HANSEN / DIRK SCHÜSSLER-LANGEHEINE (eds.), Patent Practice in Japan and Europe – Liber Amicorum for Guntram Rahn Wolters Kluwer (2011) ISBN 978-90-411-3689-3; xxiv+827 pp.; EUR 196.00